MODEL VEHICLE ROUTING PROBLEM DALAM MENGOPTIMUMKAN RUTE PENGANGKUTAN SAMPAH DI KOTA BOGOR - Widyastiti, Maya; Kamila, Isti (Jurnal Matematika, Statistika dan Komputasi, 2019)
Garbage is a common problem that often occurs in many cities, including in Bogor. Every day, the volume of garbage in Bogor reaches 600 tons and only 475 tons can be transported to the Galuga Landfill Site. However, the vehicle which is owned by the Environmental Agency of Bogor is limited and has certain capacity.In this study, we formulated garbage transportation in the form of a Vehicle Routing Problem model with Branch and Bound method and completed using LINGO 11.0. The optimal solution obtained is a garbage transport route with a minimum distance, and obtained a distance is 1583.24 km, with West Bogor is 172.6 km, Central Bogor is 344.99 km, East Bogor is 298.79 km, North Bogor is 267.4 km, South Bogor is 252.41 km and Tanah Sareal is 247.05 km. Of the six sub-districts, there was a decrease in the distance of garbage transportation from Temporary Disposal sites to the Galuga Landfill. Keywords: Garbage transportation, Optimization, Vehicle Routing Problem.